2022
DOI: 10.3390/ijerph19063234
|View full text |Cite
|
Sign up to set email alerts
|

E-Professionalism among Dental Students from Malaysia and Finland

Abstract: The increased use of social media in dentistry is associated with both advantages and disadvantages. A new form of professionalism, “e-professionalism,” has emerged. It includes an online persona and online information in any format that displays cues to professional identity, attitudes, and behaviors. The objective was to explore the perceptions of Malaysian and Finnish dental students on e-professionalism. A survey of 613 Malaysian and Finnish students was performed. The main variables assessed were posting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Possible explanations for this are that younger HCPs are more versed in how to navigate SNSs and are more accustomed to SNSs being a part of their identity [ 2 ]. This can lead them to be more error-prone and more likely to post unprofessional content [ 12 , 14 , 59 ] . This was also seen in the definitive results of the mixed methods study conducted by Vukušić Rukavina et al, which found more unprofessional content on the Facebook profiles of students (5.8%) than faculty (0%) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for this are that younger HCPs are more versed in how to navigate SNSs and are more accustomed to SNSs being a part of their identity [ 2 ]. This can lead them to be more error-prone and more likely to post unprofessional content [ 12 , 14 , 59 ] . This was also seen in the definitive results of the mixed methods study conducted by Vukušić Rukavina et al, which found more unprofessional content on the Facebook profiles of students (5.8%) than faculty (0%) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing one's need for further education is a step in the right direction, and 74.1% of our respondents stated that they would benefit from additional guidelines on e-professionalism. Exposure to problems of e-professionalism by opening debate and dialogue with HCPs at all levels to raise attention and awareness, especially on conflicting or blurred issues, could perhaps alert an even larger percentage of HCPs to the need for guidelines on e-professionalism [ 15 , 32 , 59 ]. The best example of a successful debate is the #medbikini movement, which sparked awareness, opened a debate, and led to the re-examining and directing of e-professionalism towards a new, better understanding of professionalism on SNSs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…While reviewing literature, although there are available scales and indexes in some form or another for the student population [40,52], we did not encounter a way to easily measure and scale perceptions of eprofessionalism of graduated MDs and DMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Marelić et al introduced the systematically designed SMePROF-S scale to assess medical and dental students’ attitudes toward e-professionalism ( 13 ). Their significant contribution aligns with an expanding international and national discourse, particularly in Croatia, where scholarly inquiries into the perceptions and engagement of medical and dental students with e-professionalism are becoming more prevalent ( 11 , 13 - 15 ).…”
mentioning
confidence: 83%